Principals and student achievement : what the research says - Cotton, Kathleen (Association for Supervision and Curriculum Development, 2003)
What are the direct and indirect influences of principals on student achievement? How do successful principals motivate others? What kinds of relationships do they have with parents, students, and staff? Principals and Student Achievement identifies 26 essential traits and behaviors of effective principals to show how they achieve success as instructional leaders. Based on a review of 81 key research articles from the last 20 years, this concise book examines how certain practices can affect student achievement, including: . Communication and interaction . Classroom observation and feedback to teachers . Recognition of student and staff achievement . Dedication to a safe and orderly school environment . Support of professional development of staff . Role modeling The book also reviews differences in instructional leadership between elementary and secondary principals, male and female principals, principals in high- and low-socioeconomic-status schools, and more. We all know that principals are important to student success, but few people have pinpointed exactly how they make a positive difference. At a time when principals are being asked to do more for school reform and accountability, Principals and Student Achievement provides a valuable resource for identifying what it takes to be an effective principal and, in turn, an effective school.